Race Differences in Physical Activity Uptake Within a Workplace Wellness Program: A Comparison of Black and White Employees. Issue 6 (July 2019) - Meints, Samantha M.; Yang, Heidi Y.; Collins, Jamie E.; Katz, Jeffrey N.; Losina, Elena
Purpose: To examine differences in physical activity (PA) uptake between black and white employees during a financial incentive-based workplace intervention. Design: Prospective cohort study from July 2014 to June 2015 (NCT02850094). Setting: Tertiary academic medical center. Participants: Forty-three black and 182 white nonclinical employees. Intervention: Participants self-selected or were assigned to teams. Participants completed a 24-week intervention receiving rewards for meeting weekly PA goals (increasing moderate-to-vigorous PA [MVPA] by 10% from previous week or meeting Guidelines threshold of 150 minutes of MVPA). Measures: Outcomes included weekly MVPA in minutes, average daily step counts, number of weeks meeting personal goals and the Guidelines, and Fitbit adherence in days and weeks. Analysis: We performed an analysis of covariance for each outcome, with race as the primary independent variable of interest, adjusting for demographic and health-related covariates. Results: During the intervention, blacks walked 9128 steps per day while whites walked 7826 steps per day, a difference of approximately 1300 steps ( P < .05). Blacks also demonstrated a greater uptake in both steps and MVPA from baseline than did whites, resulting in similar MVPA throughout the intervention. Conclusions: Findings suggest that workplace PA interventions using financial incentives may result in similar engagement in MVPA among white and black employees, while black employees walk more steps during the intervention. Limitations include a primarily white female sample which may not generalize.